Hyperthermia Nanofiber Platform Synergized by Sustained Release of Paclitaxel to Improve Antitumor Efficiency. Issue 13 (15th May 2019) - Niiyama, Eri; Uto, Koichiro; Lee, Chun Man; Sakura, Kazuma; Ebara, Mitsuhiro
Abstract: Effective cancer therapy can be achieved by designing a smart nanofiber system with the combination of chemotherapy and hyperthermia. This study demonstrates the in vivo antitumor effect of a nanofiber mesh that can deliver heat and antitumor drug in a controlled manner. The mesh is composed of biodegradable poly(ε‐caprolactone) (PCL) with paclitaxel (PTX) and magnetic nanoparticles (MNPs). The PCL mesh releases PTX slowly for at least 6 weeks when tested in vitro. The prolonged therapeutic effect is observed in vivo as a continuous release of medication from the mesh over an extended period of time compared with direct injection of PTX into the tumor site. In addition, the synergistic anticancer effect is achieved upon excitation of the mesh with an alternating magnetic field because the MNPs within the nanofiber generate localized heat which causes heat‐induced cell killing as well as enhanced chemotherapeutic effect of PTX. Based on these results, the smart nanofiber system may be very promising for cancer therapeutics in the future and may provide knowledge for new development of localized drug delivery. Abstract : This study demonstrates the antitumor effect of a nanofiber mesh that can deliver heat and antitumor drug in a controlled manner. The mesh generates heat when the loaded magnetic particles are activated in a magnetic field. The thermo‐chemotherapy combo displays enhanced antitumor activity and the systemic toxic effects can be eliminated due to local release of the chemotherapeutic agents.